Men`s freestyle angle of catch point, finish point and kick point - Inada, N.; Kawamoto, K.; Ide, T. (1st International Scientific Conference of Aquatic Space Activities, 2008)
This study focused on explaining the reasons for the increased timing in men`s 100 meter freestyle. Three representative freestyle sprint swimmers` angle of catch point, finish point, and kick point for last forty years were analyzed. Mark Spitz from 1970`s, Matt Biondi from 1980`s and Anthony Arvin from 2000`s were picked up for the present investigation. 1970`s, Mark Spitz used S-pattern stroke technique. 1980`s, Matt Biondi used technique of rolling the body from side to side. 2000`s, Anthony Ervin used technique of rolling only the upper body from side to side. It was concluded that future sprint freestyle champions may employ the straight arm while only rolling the upper body with a steep catch, finish and kick point angle to further enhance sprint freestyle performance.